Analysis of Legal Political Dynamics in the Regulation of Simultaneous Regional Elections in Indonesia: Between Effectiveness and Local Democracy - Ismaidar Ismaidar; Tamaulina Br. Sembiring; Yulia Christy Shintara Aruan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This paper describes the dynamics of legal politics in the regulation of Simultaneous Regional Elections in Indonesia with a focus on the effectiveness of implementation and its impact on local democracy. Simultaneous Regional Elections, which began in 2015, are the government's efforts to improve the efficiency of regional head elections while strengthening the democratic system. However, its implementation faces various challenges, such as regulatory complexity, potential political conflict, and impacts on the quality of representation at the local level. This study uses a juridical-normative approach with a qualitative analysis method to evaluate the laws and regulations governing Simultaneous Regional Elections, including Law Number 10 of 2016 and its implementing policies. Data were obtained through literature studies, legal documents, and interviews with relevant stakeholders. The results of the study show that, although Simultaneous Regional Elections bring benefits in the form of budget efficiency and strengthening political stability, this policy also poses a number of challenges. Among them are the gap in local government capacity, strengthening political oligarchy, and decreasing the quality of community participation at the local level. In addition, the implementation of Simultaneous Regional Elections tends to sacrifice regional autonomy in the context of local democracy, given the homogenization of election times that do not always match regional needs. This study recommends the need for a revision of regulations that are more adaptive to local needs, increasing public political education, and strengthening the capacity of election organizers to ensure that Simultaneous Regional Elections can run effectively without sacrificing the principles of local democracy.